Integration of Islamic Education Teaching Methods to Enhance Student Engagement in Madrasah - Niken Ayu Restiana; Bilqis Nurin Nahari; Ammar Abdurrozzaq; Cyntia Intan Okta Aulia; Okta Aulia; Moh In’ami (Sekolah Tinggi Agama Islam Solok Nan Indah, 2026)
Student engagement in Islamic education remains a central challenge in elementary madrasahs, where teaching effectiveness is shaped by the choice and integration of methods. This study aims to describe the implementation of teaching strategies and analyze the supporting and inhibiting factors influencing learning outcomes at one elementary madrasah. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, and analyzed with the Miles and Huberman interactive model. Triangulation of sources, techniques, and time was applied to ensure validity. The findings indicate that teachers employ a combination of lecture, question-and-answer, discussion, habit formation, educational games, and hands-on practice, which collectively enhance student engagement and comprehension of Islamic values. Supporting factors include teacher commitment and structured routines for religious habit formation, while inhibiting factors involve limited facilities, restricted time allocation, and underutilization of technology. The study concludes that effective Islamic education requires methodological integration, environmental support, and value-based pedagogy. The implications emphasize the need for more interactive and technology-enhanced approaches to strengthen participation and improve the quality of Islamic education at the elementary madrasah level.